(untitled) (Práxis Educativa, 2022)
The article analyzes the trajectory of black students inserted by racial quotas in Higher Education courses at the Instituto Federal Sul-rio-grandense (IFSul), campus Pelotas. A problematizing approach was carried out on racial quotas, considering the consolidation of Law no. 12,711, of August 29, 2012, which establishes guiding actions to guarantee the access and permanence of students who entered through racial quotas in this institution’s higher education courses. In this research, 11 students enrolled in Higher Education who entered through racial quotas, in the L2 and L4 modalities, were interviewed. The research methodology presents a qualitative approach, with interviews with open questions and the use of content analysis based on Bardin (2011) to interpret the interviews. It was found that students included in the racial quotas policy understand it as a policy of inclusion, valuation and social projection of the Brazilian black population, corroborating the studies of Almeida (2019), Charlot (2005, 2013) and Gomes (2017). However, despite the quotas, the presence of black students in the classroom is small, which indicates the need for other policies that address access to and permanence in Higher Education. Keywords: Higher Education. Racial quotas. Social valuation.